PENGUATAN PEMASARAN DAN BRANDING PRODUK PANGAN SEHAT POSBINDU DAHLIA INDAH MELALUI PENDEKATAN KOMUNITAS - Jeremy Putra Pratama; Taqwa Putra Budi Purnomo Sidi Hiram (Jurnal Padamu Negeri, 2025)
Posbindu Dahlia Indah is a community-based business that develops healthy food products from natural ingredients. Products such as Kunyit Asem, Kunyit Tawar, Asem Gula, Ginger Powder, and Vegetable chips are produced with an environmentally friendly approach and without preservatives. However, Posbindu faces challenges in marketing and branding, with an unoptimized e-commerce account, limited digital marketing, and less attractive product packaging. The purpose of this service is to identify and overcome marketing problems through an integrated approach between traditional, digital, and community-based marketing. The methods used are traditional and digital marketing training, as well as the development of customer loyalty programs and partnerships with healthy food stalls and shops. The results showed that through strengthening digital marketing, social media, and community partnerships, Posbindu's products were more widely recognized and received positive responses from consumers. In addition, the customer loyalty program also increases repeat orders and builds long-term relationships. The long-term benefits of this strategy are increased brand awareness, market expansion, and stronger business sustainability.